Inspection and analysis of ancient Monastery of “São Romão de Neiva”, Portugal - Villafuerte, Jahdiel (2019)
The monastery of São Romão de Neiva is an ancient building located in the north of Portugal, in the district of Viana do Castelo and it is considered to be of national interest by the Portuguese Institute of Monuments (DGPC). Due to its importance, an inspection to identify damages and their causes was performed on this building. The inspection and diagnosis included a historical, geometrical and defects survey, and mechanical and physical characterization of the masonry stone. Non-destructive tests on the structural elements such as GPR and sonic tests were also carried out to assess the internal morphology of the stone masonry walls and estimate the quality and modulus of elasticity, respectively. Qualitative assessment of masonry walls using the MQI (Masonry Quality index) was also carried out. Finally, by means of a visual inspection of the struc-ture, the assessment of the damages and pathologies on the structural elements was performed. This work focus on the most important experimental results and some recommendations to apply them on a structur-al analysis.